Layanan Bimbingan dan Konseling Berbasis Gamifikasi: Studi Literatur - Nugroho, Agung; Hariastuti, Retno Tri; Christiana, Elisabeth; Habsy, Bakhrudin All (Indonesian Journal of Educational Counseling, 2025)
Gamification is the application of elements of gaming into non-gaming situations with the aim of increasing individual participation and motivation. In the context of guidance and counseling, gamification can be used as an innovative approach to improve the quality of services, both in individual and group counseling, and in guidance programs. The purpose of this study is to 1) explore the role of gamification in guidance and counseling services, and 2) examine how its application can increase student involvement in participating in BK services. This study uses a qualitative method by analyzing various literature such as scientific articles and research results. The findings show that the use of gamification elements such as points, badges, leaderboards, and game-based challenges is able to drive student motivation and participation in BK services. In addition, this approach also supports the development of social skills, emotional management, and independence in solving problems. Therefore, gamification has great potential as an innovative method in increasing the effectiveness and attractiveness of guidance and counseling services for students.